2013
DOI: 10.1097/mco.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine in the intensive care unit

Abstract: Glutamine supplementation has been recognized as beneficial in acutely injured patients. However, recent conflicting results in either 'real-life conditions' or very severe situations suggest that its indications need to be more precisely determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Several studies have shown that a low glutamine concentration, associated with an unfavourable outcome, is valid for some 30% of ICU patients [4,5]. Comments on the REDOXS study interpretations vary widely – from ‘… should be abandoned in clinical practice’ [6] to ‘… should be reserved for specifically identified patients with compromised glutamine availability’ [7]. …”
mentioning
confidence: 99%
“…Several studies have shown that a low glutamine concentration, associated with an unfavourable outcome, is valid for some 30% of ICU patients [4,5]. Comments on the REDOXS study interpretations vary widely – from ‘… should be abandoned in clinical practice’ [6] to ‘… should be reserved for specifically identified patients with compromised glutamine availability’ [7]. …”
mentioning
confidence: 99%
“…Despite the strong physiologic evidence that critical illness increases the PR, most patients in modern ICUs are remarkably protein deprived 85 , 86 , 103 . One author even speculated that administering large doses of any single amino acid (eg, glutamine) could create distortions and toxicities in patients who are as severely protein deficient as most modern ICU patients 107 . Such a toxic effect seems unlikely, however, given the extremely low rates at which glutamine has been administered in clinical trials in comparison to its many‐fold‐greater endogenous turnover rate.…”
Section: Amino Acids As Supplements and Additivesmentioning
confidence: 99%
“…For this reason glutamine has been postulated to be an essential amino acid in the critically ill and glutamine supplementation a beneficial intervention [1]. Furthermore, it has been hypothesized that most of the positive effect of glutamine supplementation is mediated by an increase in citrulline and arginine production [2].…”
Section: Introductionmentioning
confidence: 99%